Facile and scalable fabrication of superhydrophobic PVDF membrane for the desalination of highly saline water using air-gap membrane distillation system. Issue 6 (December 2022) - Baig, Umair; Azeem, Mohammed Abdul; Lawal, Dahiru Umar; Abdulgader, Hasan Al; Baroud, Turki N.
Abstract: Here, a facile and novel route to fabricate superhydrophobic poly (vinlylidene fluoride) (PVDF) polymeric membranes for the desalination of highly saline water is described. The superhydrophobic PVDF membrane (with a high-water contact angle >150°) was fabricated by phase inversion process on a smooth glass surface followed by surface chemical modification with long fluoroalkylsilane chains (F21) via a single dip-coating approach. The superhydrophobicity of the membrane surface after F21 modification was found to be positively correlated with the concentration of the fluorine groups and the dip-coating duration. The performance of these membranes for the treatment of highly saline water was also evaluated using an air gap membrane distillation (AGMD) system. The chemically modified PVDF membrane exhibited excellent and stable salt rejection of over 99.99% (∼ 100%) and high mean water permeate flux (19.09 L/m 2 .h) when using synthetic 7 wt% NaCl feed solution. The modified PVDF membrane showed significant improvement in the mean water flux (>60%) compared to the pristine PVDF membrane due to variations in the membrane's chemical and bulk structure in the dip coating process. The results suggested that the nature and amount of the endowed fluoroalkylsilane chains on the membrane surface are key design parameters in membrane fabrication for stable and excellent-performing membranes for desalinating highly saline water. Graphical Abstract: ga1 Highlights: Facile and scalable fabrication of super-hydrophobic PVDF membranes. Applied for desalination of highly saline water using AGMD system. PVDF membrane with long fluoroalkylsilane chains (F21) modification showed excellent desalination performance.